Membranous β-Catenin Expression Inversely Correlates with WHO/ISUP Grading in Clear Cell Renal Cell Carcinoma: An Indonesian Cross-Sectional H-Score Study - Rifka Ulfa Rosyida; Kenty Wantri Anita; Ihda Dian Kusuma; Eviana Norahmawati; Rachmad Sarwo Bekti (HM Publisher, 2026)
Background: Clear cell renal cell carcinoma (ccRCC) is the most common adult renal malignancy and exhibits heterogeneous clinical behavior that is currently stratified by the WHO/ISUP nuclear grading system. β-catenin, the terminal effector of canonical Wnt signaling and an integral component of the cadherin–catenin adhesion complex, has been implicated in epithelial–mesenchymal transition (EMT) and tumor progression, but its quantitative relationship with WHO/ISUP grade in Indonesian ccRCC has not been reported. Methods: This analytic observational cross-sectional study examined 73 archived formalin-fixed, paraffin-embedded ccRCC specimens collected at the Anatomical Pathology Installation of Dr. Saiful Anwar Regional General Hospital Malang between January 2019 and May 2025. Immunohistochemistry for β-catenin (Dako Clone 14, dilution 1:200) was scored independently and blindly by two anatomical pathologists using the H-score methodology across ten 400× high-power fields per case. Results: The overall mean H-score was 236.4 ± 50.6 (range 20–295). Spearman rank correlation revealed a strong, statistically significant inverse association between membranous β-catenin H-score and WHO/ISUP grade (ρ = –0.664; 95% CI –0.778 to –0.503; p < 0.001). Mean H-scores declined monotonically from Grade 1 (285 ± 28) through Grade 2 (270 ± 32), Grade 3 (228 ± 30), to Grade 4 (175 ± 32), and Receiver Operating Characteristic analysis distinguished high-grade (G3–G4) from low-grade (G1–G2) tumors with an area under the curve of 0.84. Conclusion: These findings support membranous β-catenin H-score as a biologically grounded, accessible immunohistochemical adjunct to WHO/ISUP grading and motivate further translational evaluation of the Wnt/β-catenin pathway as a stratification and therapeutic target in ccRCC.